2004
DOI: 10.1021/ja048342i
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Crystal Structure and Mobility in Organic Field-Effect Transistors Based on Single Crystals of Tetrathiafulvalene Derivatives

Abstract: Recently, it was reported that crystals of the organic material dithiophene-tetrathiafulvalene (DT-TTF) have a high field-effect charge carrier mobility of 1.4 cm(2)/(V x s). These crystals were formed by a simple drop-casting method, making this material interesting to investigate for possible applications in low-cost electronics. Here, organic single-crystal field-effect transistors based on materials related to DT-TTF are presented and a clear correlation between the crystal structure and the electrical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
245
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(261 citation statements)
references
References 44 publications
12
245
0
4
Order By: Relevance
“…To the best of our knowledge, this is the highest mobility for n-channel transistors based on organic single crystal wires prepared by solution processing. It is comparable with the highest mobility of p-channel organic wires prepared by solution processing (20)(21)(22), as well as to the best performance of n-channel single-crystal organic transistors prepared with a free-space gate dielectric (43). Additionally, this mobility is approximately 10 times higher than that of vacuum-evaporated thin-film devices (0.1 cm 2 /Vs) of the same molecules (39).…”
Section: (See Materials and Methods)supporting
confidence: 56%
See 2 more Smart Citations
“…To the best of our knowledge, this is the highest mobility for n-channel transistors based on organic single crystal wires prepared by solution processing. It is comparable with the highest mobility of p-channel organic wires prepared by solution processing (20)(21)(22), as well as to the best performance of n-channel single-crystal organic transistors prepared with a free-space gate dielectric (43). Additionally, this mobility is approximately 10 times higher than that of vacuum-evaporated thin-film devices (0.1 cm 2 /Vs) of the same molecules (39).…”
Section: (See Materials and Methods)supporting
confidence: 56%
“…These unique materials combine the high-performance of singlecrystalline structures with solution-processability by dispersion (17,18). Several p-channel (hole-transporting) organic wires prepared by solution-processing have exhibited Ͼ 0.1 cm 2 /Vs for singlewire transistors (19)(20)(21)(22), whereas only a few solution-synthesized n-channel organic wires have been reported, typically with low performance ( Ϸ10 Ϫ3 Ϫ 10 Ϫ2 cm 2 /Vs) (23,24).Despite the intrinsic high mobility of single-crystalline wires, precise wire placement and wire-to-wire performance variation, due to the difference in the contact quality at the wire/insulator and wire/electrode interfaces, substantially hinder successful device integration (10, 25). Therefore, the technology to achieve network films of organic MWs deposited from a dispersion with controlled alignment and density is acutely desired.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was pointed out that the higher solubility of these materials should be advantageous for their use in low-cost solution processing [57]. In fact, SC-OFETs were fabricated by solution processing for some kinds of TTF analogues [64][65][66][67].…”
Section: Sc-ofets Of Ttf Analoguesmentioning
confidence: 99%
“…These derivatives exhibit excellent charge transfer properties, the highest charge mobility of which was reported to be 3.6 cm 2 /(V s) [16]. Mas-Torrent et al [17,18] studied dithiophene-tetrathiafulvalene (DT-TTF) and dibenzo-tetrathiafulvalene (DB-TTF), which contain similar molecules but present different crystal packing types, and found that different intermolecular interactions significantly influence the electronic transport properties of the compounds. Naraso et al [19] found that OFET devices based on halogeno-substituted quinoxaline rings fused with TTF show excellent n-type performance and high carrier mobility.…”
mentioning
confidence: 99%